Business Development Strategy For Mung Collection Using Digital Marketing - Christian, Fernando Marcio; Wibowo, Januar; Fianto, Achmad Yanu Alif; Candraningrat, Candraningrat (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
The role of retail businesses in helping the national economy grow is by opening up job opportunities for the surrounding community and also building a reseller network. Now retail business activities vary widely and some are still conventional to online. Mung Collection is a trading business that sells bedroom equipment products, namely bed linen, bed covers, and blankets. The business development method that Mung Collection will carry uses the 4P Marketing Mix strategy (Prioduct, Price, Place, and Promotion), BMC, and SWOT analysis to support for digital marketing. Develop marketing strategies and implement them in online marketing media on the Website, WhatsApp, Instagram, Facebook, TikTok, and Shopee Mung Collection to increase Mung Collection sales in the future.